Elucidating the Relationship Between Diabetes Mellitus and Parkinson’s Disease Using 18F-FP-(+)-DTBZ, a Positron-Emission Tomography Probe for Vesicular Monoamine Transporter 2 - Kong, Yanyan; Zhou, Haicong; Feng, Hu; Zhuang, Junyi; Wen, Tieqiao; Zhang, Chencheng; Sun, Bomin; Wang, Jiao; Guan, Yihui (Frontiers in Neuroscience, 2020)
Diabetes mellitus (DM) and Parkinson disease (PD) have been and will continue to be two common chronic diseases globally, which are difficult to diagnose during the prodromal phase. Current molecular genetics, cell biological, and epidemiological evidences have shown the correlation between Parkinson disease and diabetes mellitus. PD share the same pathogenesis pathways and pathological factors with DM. In addition, BETA-cells reduction can cause hyperglycemia which is a striking feature of diabetes. Recent studies indicated that hyperglycemia was highly relevant to the pathologic changes in PD. However, further correlation between diabetes mellitus and Parkinson disease remains to be investigated. Intriguingly, polycystic monoamine transporter 2 (VMAT2) is co-expressed in dopaminergic neurons and BETA cells, which is responsible for taking up DA into presynaptic vesicles and can specific binding to BETA cells. And we summarized the specific molecular and diagnostic functions of VMAT2 in two diseases in this review. Therefore, VMAT2 can be applied as a target probe for positron emission tomography (PET) imaging to detect BETA-cell and dopamine level changes, which can definitely contribute to diagnosis diabetes mellitus and Parkinson disease during the prodromal phase. Targeting VMAT2 with the molecular probe 18F-FP-(+)-DTBZ can be used as an entry point from the BCM changes of DM at the molecular level to clarify the potential relationship between DM and PD. It has promising clinical significance in investigating the pathogenesis, early diagnosis, and treatment evaluation of the two diseases.